Theoretical Prediction of Monolayer BeP2O4H4 with Excellent Nonlinear‐Optical Properties in Deep‐Ultraviolet Range - Liu, Xin; Wu, Li‐Ming; Kang, Lei; Lin, Zheshuai; Chen, Ling (Small (Weinheim an der Bergstrasse, Germany), 2024)
Most 2D nonlinear optical (NLO) materials do not have an ultrawide bandgap, therefore, they are unsuitable for working in the deep‐ultraviolet spectral range (< 200 nm). Herein, the theoretical prediction of an excellent monolayer BeP2O4H4 (ML‐BPOH) is reported. DFT analyses suggest a low cleavage energy (≈45 meV per atom) from a naturally existed bulk‐BPOH material, indicating feasible exfoliation. This novel 2D material exhibits excellent properties including an ultrawide bandgap (Eg) of 7.84 eV, and a strong second‐order nonlinear susceptibility (dbulkeff$d_{bulk}^{eff}$ = 0.43 pm V−1), which is comparable to that of benchmark bulk‐KBBF crystal (d16 = 0.45 pm V−1). The wide bandgap and large SHG effect of ML‐BPOH are mainly derived from the (PO2H2)− tetrahedron. Notably, ML‐BPOH exhibits an outstanding 50% variation in dsheet under minor stress stimuli (±3%) due to rotation of structurally rigid (PO2H2)− tetrahedron. This indicates significant potential for application in material deformation monitoring. The theoretical prediction of an excellent DUV SHG 2D material, monolayer BeP2O4H4 (ML‐BPOH) characterized by a low cleavage energy from a naturally existing bulk‐BPOH is reported. Notably, ML‐BPOH exhibits an outstanding 50% variation in dsheet (Å·pm V−1) under minor stress stimuli (±3%), indicating a potential for application in material deformation monitoring.